HOW â€œTRADITIONALâ€ ARE SO-CALLED TRADITIONS? : THREE CASE STUDIES OF MALAYAN FOLK PERFORMANCE - Ross, Lawrence (Jurnal Pengajian Melayu (JOMAS), 2020)
This article challenges perceptions of “traditions” as being longstanding and unchanged practices by showing several cases in which so-called traditional musical genres were created relatively recently, and reworked over time, partly in response to prevailing social trends. Through musicological and ethnographic methods, this study ascertains sources for local musical repertoires, and situates them as forms of expression within their particular communities. The locus of this study is the border region shared between Malaysia and Thailand, where rural communities — whose social patterns are often under prolonged, and often changing external hegemonic pressures — have managed a complex array of identities and affiliations. The three case studies included here are (1) an idiomatic form of Malayan ronggeng social dance called rong ngeng, created in the 1940s and ’50s by Thaispeaking performers in Krabi Province; (2) main berana, an evolving repertoire of songs performed by Andaman Coast Orak Lawoi ‘sea people,’ for their festive rituals; and (3) gendang silat ‘martial arts musical accompaniment’ performed in Malaysia’s Kedah State. This study finds that, despite the ambiguous historical meaning that musical traditions hold for the people that perform them, they are a window into understanding how local communities navigate social changes, and possible indicators for future trends of expression.